Pengaruh Efektifitas Kelas Industri, Profesional Guru dan Minat Kerja terhadap Kesiapan Kerja Siswa SMK Kabupaten Kebumen - Supriyadi, Bambang; Purbonuswanto, Welius (Media Manajemen Pendidikan, 2024)
This study aims to determine the effect of Industrial Class Effectiveness, Teacher Professionalism and Work Interests together on Work Readiness of State Vocational School Students in Kebumen Regency, and to determine the effect of Industrial Class Effectiveness, Teacher Professionals and Work Interests individually on Work Readiness. Students of State Vocational Schools in Kebumen Regency. This research was conducted at SMK Negeri 1 Kebumen, SMK Negeri 1 Karanganyar, and SMK Negeri 1 Ambal. The research period was November 2020 to January 2021. This research used a correlational quantitative approach with a population of 108 students. The sample was determined as many as 85 students who were taken using the cluster random sampling method. The data analysis included descriptive analysis, data analysis prerequisite test analysis and hypothesis testing. The results of this study indicate that the work readiness variable is influenced by the industrial class effectiveness variable by 30.7%, the professional teacher variable by 16% and the work interest variable by 35.8% and of the three variables together is 82.5% so that there are 17.5% other factors that can affect job readiness but not examined in this study. Therefore, it is hoped that in further research, other factors can be found that can affect student work readiness.